Manejo agronómico del palto (persea americana.mill) variedad hass en CHAO – LA LIBERTAD - Gutiérrez Ramírez, Alex Humberto (2013)
The agronomical management of avocado variety Hass in the area of Chao, freedom begins with the leveling of the ground using D7 and D8 crawler tractors and farm tractors with leveling rufous. Pressurized irrigation system installation is performed once levelled the ground and allowing us to wash field cultivation and planting of windbreaks living salts. After these two processes is the marking of field for the incorporation of organic matter and drip hose placed. Taking the field with irrigation hoses and incorporated organic matter proceed to alternate crops such as the beans and barley; Once structured field proceeds to make the holes and then to the plantation. After established planting proceeds to the underpinning or change of plants that failed to settle, with another new one. In fields of two years is already pruning baseline and in some cases training. Pruning of production occurs after the first harvest in order to obtain greater production and this is accompanied by a good phytosanitary control and turn of irrigation proper as well as fertilization with the necessary quantities for the production of the plant and at the right time. Avocado crop management completes with the harvest where reflected the outcome of all the activities carried out prior to this.